Penguatan budaya literasi sekolah: Kolaborasi dosen dan siswa dalam program MBKM UIN Salatiga - Sari Famularsih; Elka Melviyana (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
School literacy culture plays a crucial role in developing critical thinking skills, character, and learning habits. However, students' interest in reading and the use of reading materials in schools still require strengthening. This community service activity aims to strengthen school literacy culture through collaboration between lecturers and students in the UIN Salatiga Teaching Assistance MBKM Program at SMP Negeri 4 Salatiga. The activity was implemented using a school-based, participatory approach and focused on utilizing the MBKM student send-off as an educational space, marked by the distribution of reading books by field supervisors to the school. The implementation method included coordination with the school, implementation of the student send-off activity, distribution of reading books, and observation of student and school responses. The results of the activity demonstrated student enthusiasm for reading books, the emergence of positive attitudes toward reading activities, and the school's commitment to utilizing books in the development of reading corners and sustainable literacy activities. This activity demonstrates that simple literacy interventions implemented contextually and collaboratively through the MBKM Program can significantly contribute to strengthening the school's literacy ecosystem.